2012
DOI: 10.1055/s-0032-1316476
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Priorities in the Management of HIV/HBV and HIV/HCV Coinfection in Resource-Limited Settings

Abstract: Liver disease due to chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infection is now emerging as an increasing cause of morbidity and mortality in human immunodeficiency virus- (HIV-) infected persons in resource-limited settings (RLS). Existing management guidelines have generally focused on care in tertiary level facilities in developed countries. Less than half of low-income countries have guidance, and in those that do, there are important omissions or disparities in recommendations. There are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 44 publications
(59 reference statements)
0
39
0
1
Order By: Relevance
“…Recent longitudinal cohort studies have found that coinfection with HBV also can lead to increased rates of progression to acquired immune deficiency syndrome (AIDS)-related outcomes and all-cause mortality 4344. An estimated 5% to 15% of the 34 million HIV-infected individuals worldwide are coinfected with HBV, as a chronic infection 4546. The burden of coinfection is greatest in Southeast Asia and sub-Saharan Africa 6.…”
Section: Epidemiology: Incidence and Prevalencementioning
confidence: 99%
“…Recent longitudinal cohort studies have found that coinfection with HBV also can lead to increased rates of progression to acquired immune deficiency syndrome (AIDS)-related outcomes and all-cause mortality 4344. An estimated 5% to 15% of the 34 million HIV-infected individuals worldwide are coinfected with HBV, as a chronic infection 4546. The burden of coinfection is greatest in Southeast Asia and sub-Saharan Africa 6.…”
Section: Epidemiology: Incidence and Prevalencementioning
confidence: 99%
“…1,2 Worldwide, an estimated 31·4–35·9 million people have HIV/AIDS, 350–400 million people have HBV, and 150–170 million have HCV. 35 These viruses share routes of transmission and many people with HIV are co-infected with HBV and HCV, especially in some populations such as injection drug users and men who have sex with men. 68 The prevalence of HBV co-infection ranges from 5% to 20% and HCV co-infection ranges from 5% to 15% in resource-limited regions.…”
Section: Introductionmentioning
confidence: 99%
“…68 The prevalence of HBV co-infection ranges from 5% to 20% and HCV co-infection ranges from 5% to 15% in resource-limited regions. 3 In New York City, the prevalence of HIV and HBV co-infection is 4·5%, that of HIV and HCV co-infection is 25·0%, and that of triple infection (HIV, HBV, and HCV) is 1·6%. 9 The transmission routes and epidemiology of HBV and HCV in people with HIV differ between low-income and high-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…As HIV-infected persons continue to live longer due to increased uptake of antiretroviral therapy (ART), liver disease has emerged as a leading cause of morbidity and mortality in HIV-infected persons coinfected with HBV or HCV [914]. Two recent complementary systematic reviews and meta-analyses have provided updated regional estimates of HIV–HBV and HIV–HCV coinfection across five different population groups [15 ▪▪ ,16 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%